PENGARUH TENAGA KERJA PEREMPUAN PENJUAL TIRAM TERHADAP PENDAPATAN RUMAH TANGGA DI KABUPATEN BARRU - Fitriany Fitriany (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to determine the effect of oyster sellers of Labor Women Against Household Income in the Village District of Barru. This study uses the labor of women oyster sellers as independent variables and the household income as the dependent variable. The population in this study is the overall female housewife of Barru as many as 50 people and research samples was determined at 28 people. To facilitate data collection, the researcher using observation, documentation, and interviews. The data analysis technique used is a simple regression analysis. Results of analysis in this study theorized that women's employment oyster sellers significantly affect household income in the village of Barru because the value of T-count is greater than the value of the T-table (17.848> 1.68) and a significance value <from 0,05.dan, contributing its influence is approximately 93%.